Liquid Crystals: Fast‐and‐Giant Photorheological Effect in a Liquid Crystal Dimer (Adv. Mater. Interfaces 9/2019). Issue 9 (9th May 2019) - Aya, Satoshi; Salamon, Péter; Paterson, Daniel A.; Storey, John M. D.; Imrie, Corrie T.; Araoka, Fumito; Jákli, Antal; Buka, Ágnes
Abstract : In article number1802032 Satoshi Aya, Fumito Araoka, Antal Jákli, and coworkers demonstrate that a liquid crystal dimer can work as a switchable photorheological material between a solid (shown in orange) and liquid crystal (blue) states by shining a ultraviolet (UV) light (purple). The photorheological switching is based on a geometrical variation in the molecular shape of the dimer. In the image, shown are a solid state at its straight molecular shape and a liquid crystal state at its double kinked shape, which is caused by an illumination of a UV light.